Failure criteria evaluation of steel pipe elbows in nuclear power plant piping systems using cumulative damage models. (January 2023) - Kim, Sung-Wan; Jeon, Bub-Gyu; Hahm, Dae-Gi; Kim, Min-Kyu
Abstract: A steel pipe elbow is an important component in the piping system of a nuclear power plant. Accordingly, its structural performance requires a piping system with high-structural integrity, especially when it is subjected to seismic loads. This component fails when subjected to cyclic loads, such as earthquakes, because of low-cycle fatigue in conjunction with ratcheting. Therefore, steel pipe elbows in piping systems should exhibit sufficient strength, ductility, and energy dissipation capacity characteristics to withstand seismic loads. In this study, various cumulative damage models were used to express quantitatively the failure criteria of the actual failure mode of an SCH40 steel pipe elbow. Experiments were performed until the point of leakage via fatigue cracking, which is the actual failure mode of steel pipe elbows, and in-plane cyclic bending was performed by using displacement control. Based on the experimental results, damage indices were calculated by using various cumulative damage models that considered ductility, energy dissipation, and their combination. Consequently, it was confirmed that the Banon index can express quantitatively the failure criteria for the leakage caused by fatigue cracking. Highlights: In-plane cyclic bending was utilized to examine the behavior of the steel pipe elbows under cyclic loads. Failure criteria for the limit state of the steel pipe elbows were expressed using cumulative damage models. The models considered ductility, energy dissipation, and the combination of ductility and energy dissipation. A method was presented to quantitatively express the failure criteria of a steel pipe elbow.